2019
DOI: 10.3390/su11195199
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Fire-Damaged Reinforced Concrete Flexural Members: A Review

Abstract: The mechanical properties of both concrete and steel reinforcement, and the load-bearing capacity of reinforced concrete (RC) structures are well known to be temperature-sensitive, as demonstrated by the severe damage that major fires cause in buildings, followed—in extreme cases—by their collapse. Since in most cases RC structures survive a fire, retrofitting fire-damaged RC members is a hot subject today. In this paper, after a recall on the performance of RC beams and slabs in fire, different repair techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…e steel jacketing prevented concrete spalling while increasing the ultimate load capacity. According to Ma et al [64], the suitable methods for repairing fire-damaged concrete structures are externally bonded reinforcement, near surface-mounted fibre-reinforced polymers, bolted side plating, jacketing with high-performance and ultrahigh-performance concretes or mortars, and replacement of the damaged concrete.…”
Section: Assessment and Rehabilitation Of Fire-damaged Precastmentioning
confidence: 99%
See 1 more Smart Citation
“…e steel jacketing prevented concrete spalling while increasing the ultimate load capacity. According to Ma et al [64], the suitable methods for repairing fire-damaged concrete structures are externally bonded reinforcement, near surface-mounted fibre-reinforced polymers, bolted side plating, jacketing with high-performance and ultrahigh-performance concretes or mortars, and replacement of the damaged concrete.…”
Section: Assessment and Rehabilitation Of Fire-damaged Precastmentioning
confidence: 99%
“…Externally bonded reinforcement (ii) Fibre-reinforced polymers (iii) Bolted side plating (iv) Jacketing with high-and ultra-high-performance concretes or mortars (v) Damaged concrete replacement Ma et al[64] …”
mentioning
confidence: 99%
“…However, survey data indicated that few RC structures collapsed in or after a fire, and most structures had their residual bearing capacity to keep working [4][5][6][7]. Furthermore, most capacities of fire-damaged structures could be restored to a normal level by proper strengthening methods [8,9]. Therefore, it is essential and urgent to develop efficient strengthening solutions for fire-damaged structures and investigate the structural behavior after that.…”
Section: Introductionmentioning
confidence: 99%